Kajian Pengembangan Dry Port Jebres Guna Mendukung Pergerakan Angkutan Barang dengan Mempertimbangkan Tingkat Pelayanannya - Wisnu Wardhana A.S; Bambang Riyanto; Bagus Hario Setiadji (Jurnal Pembangunan Wilayah dan Kota, 2021)
The existing railway network connecting Jebres Dry Port with Tanjung Emas Port is expected to support the mobility of goods within its area of service known to have a high potential. However, the progress of Jebres Dry Port has not been fully maximized as expected due to various obstacles and issues in its development. Therefore, this research aims to evaluate the service level, influencing factors, and formulate the development strategy of goods transportation in Dry port Jebres. The data was collected through observation and questionnaire method, and for Importance Performance Analysis method for service level was used for the variable of six key drivers in Sislognas (National Logistic System), and SWOT analysis to formulate the development strategy. The analysis of service level of Jebres Dry port indicated that generally the respondent is not satisfied with the goods transportation through Jebres Dry Port. Furthermore, the internal and external factors analysis revealed that IFAS = 1,824 and EFAS = 2,780, where the appropriate strategy for Jebres Dry Port development is harvest or divest (Quadrant VI, Matrix I-E). The strategy that can be developed is by using existing competitive advantage to exploit available market potentials. In the short term, the development strategy is made by improving the service for customers by improving the main priority indicators resulted from the analysis. In the long term in the future, it is still possible to relocate Jebres Dry Port.